Individuals in international humanitarian law : a historical analysis - Landefeld, Sarina (Oxford ; New York : Hart Publishing, 2025)
"This book offers a new, more critical perspective on the regulation and protection of individuals under international humanitarian law. Providing a historical account of the changing concept of individuals since 1864, the study draws on social constructivism, casting a light on the struggle of making sense of, and agreeing on, the position of individuals in armed conflicts, often hidden by international humanitarian law's conventional narratives"--
Constructing Individuals for International Humanitarian Law -- The Early Written Laws of War -- The Inter-war Years and the 1949 Geneva Conventions -- From the 1949 Geneva Conventions to the 1977 Additional Protocols -- The Post-1977 Era.
BIBINDX
Keywords: Humanitarian law -- History